Perkembangan Pelabuhanan Merak Sebagai Pusat Perdagangan dan Pelayaran di Indonesia 1912-2009 - Putri, Viona Audia; Susnayanti, Susnayanti; Purnomo, Budi (LP4MK STKIP PGRI Lubuklinggau, 2023)
The Merak crossing port route, which connects the islands of Java and Sumatra and is in the city of Cilegon in the province of Banten and is also the busiest crossing in Indonesia, serves as a traffic gateway. In 1912, Merak Harbor saw its first use. Merak Harbor was a spearheading ship port underlying 1912 by the Dutch East Indies government. Before becoming a national asset of Indonesia, the port served colonial political purposes when it was built. The presence of this port is a financial resource for Banten region which has an ocean transportation strategy heading with the point and objective of turning into